Nanostructured spinet ZnCo2O4 for the detection of LPG - Vijayanand, Subramanian; Joy, Pattayil Alias; Potdar, Hari S.; Patil, Dewyani; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
Nanostrucutred spinel ZnCo2O4 (similar to 26-30 nm) was synthesized by calcining the mixed precursor (consisting of cobalt hydroxyl carbonate and zinc hydroxyl carbonate) in air at 600 degrees C for 5 h. The mixed precursor was prepared through a low cost and simple co-precipitation/digestion method. The transformation of the mixed precursor into nanostructured spinel ZnCO2O4 upon calcinations was confirmed by X-ray diffraction (XRD) measurement, thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) and high resolution transmission electron microscopy (HRTEM). To demonstrate the potential applicability of ZnCo2O4 spinel in the fabrication of gas sensors, its LPG sensing characteristics were systematically investigated. The ZnCo2O4 spinel exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 72-50 ppm LPG gas at 350 degrees C), response time (similar to 85-90 s), recovery time (similar to 75-80 s), excellent repeatability, good selectivity and relatively lower operating temperature (similar to 350 degrees C). The experimental results demonstrated that the nanostructured spinel ZnCo2O4 is a very promising material for the fabrication of LPG sensors with good sensing characteristics. Plausible LPG sensing mechanism is also discussed. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: HRTEM; LPG sensor; Nanostructured ZnCo2O4; Semiconductor gas sensors; XPS